Building Religious Moderation Through Faith Based Education: A Comparative Case Study of Islamic and Christian Secondary Schools in Jember, Indonesia - Imam Ahmad Aminul; Muh. Azhar Kholidi (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2026)
Indonesia’s religiously plural society faces growing challenges from religious conservatism and intolerance, making faith-based education a critical site for cultivating religious moderation. However, empirical comparative research examining how different faith traditions operationalize moderation in secondary schools remains scarce. This study aims to examine and compare the conceptualization and implementation of religious moderation in an Islamic and a Catholic secondary school in Jember, East Java, Indonesia, and to synthesize an integrated framework applicable across diverse religious educational contexts. This qualitative comparative case study employed semi-structured interviews with 31 participants, 160 hours of participant observation, and document analysis over six months (August 2024–January 2025) at SMA Muhammadiyah 3 Jember and SMAK Santo Paulus Jember. Findings reveal that both schools ground moderation in theologically authentic frameworks—the Islamic school through wasatiyyah and ukhuwah principles, the Catholic school through Catholic social teaching and MSC spirituality—while demonstrating convergent strategies of experiential interfaith learning, critical pedagogy, and community engagement. The study synthesizes a five-dimensional framework for religious moderation in faith-based education: theological grounding, curricular integration, pedagogical innovation, institutional culture, and community partnership. These findings demonstrate that strong confessional identity and genuine pluralistic engagement are compatible, offering practical guidance for educators and policymakers.